2019
DOI: 10.3389/fnins.2019.00618
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Rapid Fluctuations of Resting State Functional Connectivity in Demyelinating, Neurodegenerative, and Psychiatric Conditions: From Static to Time-Varying Analysis

Abstract: Functional magnetic resonance imaging (fMRI) at resting state (RS) has been widely used to characterize the main brain networks. Functional connectivity (FC) has been mostly assessed assuming that FC is static across the whole fMRI examination. However, FC is highly variable at a very fast time-scale, as demonstrated by neurophysiological techniques. Time-varying functional connectivity (TVC) is a novel approach that allows capturing reoccurring patterns of interaction among functional brain networks. Aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 150 publications
(306 reference statements)
1
19
3
Order By: Relevance
“…An fMRI study on rheumatoid arthritis (RA) indicated that fatigue was related to mPFC-DAN FC (25). Psychology literatures have also documented the close relationship between fatigue and DAN (39,40). We validated the above findings and further suggested that the left inferior temporal cortex rather than the whole DAN is connected to mPFC in AS.…”
Section: Discussionsupporting
confidence: 73%
“…An fMRI study on rheumatoid arthritis (RA) indicated that fatigue was related to mPFC-DAN FC (25). Psychology literatures have also documented the close relationship between fatigue and DAN (39,40). We validated the above findings and further suggested that the left inferior temporal cortex rather than the whole DAN is connected to mPFC in AS.…”
Section: Discussionsupporting
confidence: 73%
“…Brain network dynamics have also been linked to various psychiatric and neurological disorders. However, almost all reported studies so far have focused on group-level comparisons between patients and healthy controls (15). Similarly, research into the role of mental illness in cognitive functions is also predominantly based on case versus control comparisons or clinical subgroup contrasts (16).…”
Section: Introductionmentioning
confidence: 99%
“…While these results must be considered exploratory, given the training limitations and the potential dFNC pitfalls described elsewhere 2,4,12 and the presence of results not surviving to FDR correction, this study suggests that 2-week AOT might be able to promote clinical improvements and modulate dFNC of sensorimotor and cognitive networks.…”
Section: Discussionmentioning
confidence: 80%